Hypoxia- or PDGF-BB-dependent paxillin tyrosine phosphorylation in pulmonary hypertension is reversed by HIF-1α depletion or imatinib treatment - Veith, Christine; Zakrzewicz, Dariusz; Dahal, Bhola Kumar; Bálint, Zoltán; Murmann, Kirsten; Wygrecka, Malgorzata; Seeger, Werner; Schermuly, Ralph Theo; Weissmann, Norbert; Kwapiszewska, Grazyna (Thrombosis and Haemostasis, 2014)
Chronic exposure to hypoxia induces a pronounced remodelling of the pulmonary vasculature leading to pulmonary hypertension (PH). The remodelling process also entails increased proliferation and decreased apoptosis of pulmonary arterial smooth muscle cells (PASMC), processes regulated by the cytoskeletal protein paxillin. In this study, we aimed to examine the molecular mechanisms leading to deregulation of paxillin in PH. We detected a time-dependent increase in paxillin tyrosine 31 (Y31) and 118 (Y118) phosphorylation following hypoxic exposure (1 % O2) or platelet-derived growth factor (PDGF)-BB stimulation of primary human PASMC. In addition, both, hypoxia- and PDGF-BB increased the nuclear localisation of phospho-paxillin Y31 as indicated by immunofluorescence staining in human PASMC. Elevated paxillin tyrosine phosphorylation in human PASMC was attenuated by hypoxia-inducible factor (HIF)-1α depletion or by treatment with the PDGF-BB receptor antagonist, imatinib. Moreover, we observed elevated paxillin Y31 and Y118 phosphorylation in the pulmonary vasculature of chronic hypoxic mice (21 days, 10 % O2) which was reversible by imatinib-treatment. PDGF-BB-dependent PASMC proliferation was regulated via the paxillin-Erk1/2-cyclin D1 pathway. In conclusion, we suggest paxillin up-regulation and phosphorylation as an important mechanism of vascular remodelling underlying pulmonary hypertension.Note: Parts of the doctoral thesis of Christine Veith are integrated into this report.
Keywords: Pulmonary arterial smooth muscle cells; cytoskeletal proteins; pulmonary hypertension; pulmonary vascular remodelling